2017
DOI: 10.1038/srep40756
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive platform for the analysis of ubiquitin-like protein modifications using in vivo biotinylation

Abstract: Post-translational modification by ubiquitin and ubiquitin-like proteins (UbLs) is fundamental for maintaining protein homeostasis. Efficient isolation of UbL conjugates is hampered by multiple factors, including cost and specificity of reagents, removal of UbLs by proteases, distinguishing UbL conjugates from interactors, and low quantities of modified substrates. Here we describe bioUbLs, a comprehensive set of tools for studying modifications in Drosophila and mammals, based on multicistronic expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 89 publications
2
61
0
Order By: Relevance
“…All together, these results show that LUZP1 levels are sensitive to degradation via the UPS pathway and suggest that truncated SALL1 may contribute to this process. Furthermore, we compared LUZP1 ubiquitination in 293 WT vs 293 335 cells using the BioUb strategy (see Materials and Methods) (44). We could observe a prominent band in presence of BioUb, likely corresponding to the monoubiquitinated form of LUZP1 in the pulldowns (Figure 7G).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All together, these results show that LUZP1 levels are sensitive to degradation via the UPS pathway and suggest that truncated SALL1 may contribute to this process. Furthermore, we compared LUZP1 ubiquitination in 293 WT vs 293 335 cells using the BioUb strategy (see Materials and Methods) (44). We could observe a prominent band in presence of BioUb, likely corresponding to the monoubiquitinated form of LUZP1 in the pulldowns (Figure 7G).…”
Section: Resultsmentioning
confidence: 99%
“…All constructs were verified by Sanger sequencing. Plasmids CAG-BioUBC(x4)_BirA_V5_puro (called here BioUb) and CAG-BirA-puro (called here BirA) were reported previously (44).…”
Section: Methodsmentioning
confidence: 99%
“…57,68 In addition, previous proteomic analyses indicated hundreds of potential substrates. 67,69,70 Therefore, it is essential to identify key ufmylated substrates that are involved in the timing of progression to mitosis, which will greatly expand our knowledge of this UBL and facilitate a better understanding of the exact molecular pathogenesis of ufmylation-related microcephaly. 67,69,70 Therefore, it is essential to identify key ufmylated substrates that are involved in the timing of progression to mitosis, which will greatly expand our knowledge of this UBL and facilitate a better understanding of the exact molecular pathogenesis of ufmylation-related microcephaly.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin fold modifier 1 (UFM1) is a ubiquitin-like protein (UBL) that has a role in several cellular processes, including unfolded-protein response and erythroid development (1)(2)(3)(4)(5)(6)(7). Recently, it has been shown that prevention of that modification leads to severe anemia that, in mice, is lethal to embryos (8).…”
mentioning
confidence: 99%